A Knowledge Organization System for the Development of an ISO 19152:2012 LADM Valuation Module. - Çağdaş, V. (2020)
The challenge to develop interactive information services for new domains is supported by Knowledge Organization Systems and Services (KOS), which model the underlying semantic structure of a domain through classification systems, thesauri, gazetteers, or ontologies. The ISO 19152:2012 Land Administration Domain Model (LADM) is an international standard regarding the management of information about ownership, value and use of land. The current version of LADM addresses legal and administrative aspects; the standard revision starts in 2017, according to ISO’s periodic maintenance procedure. A group of researchers have initiated the development of a valuation component of LADM in terms of a draft extension module. It concerns the fiscal parties involved in the valuation practices and fiscal real property units that are the objects of valuation (see Çağdaş et al., 2016). The present paper aims at supporting this initiative by providing a domain vocabulary and thesaurus. The presented Valuation Thesaurus is developed according to the ANSI/NISO Z.39.19-2005 ‘Guidelines for the Construction, Format, and Management of Monolingual Controlled Vocabularies’ and includes terms derived from international valuation standards, such as European Valuation Standards (TEGoVA, 2012), International Valuation Standard (IVSC, 2013), Standard on Mass Appraisal of Real Property (IAAO, 2013a), Standard on Automated Valuation Models (2003), Standard on Ratio Studies (IAAO, 2013b). It is encoded through the Simple Knowledge Organization Systems (SKOS) specifications developed by World Wide Web Consortium (W3C) for standardized representation of structured vocabularies. The Valuation Thesaurus reveals the core semantic of the immovable property valuation domain, and therefore supports the identification of candidate classes, class attributes and relationships for the further elaboration of the mentioned LADM Valuation Module